Hutan Dibabat, Masyarakat Melarat, Masa Depan Gelap Refleksi Teologis atas Keberpihakan Gereja Terhadap Masyarakat dalam Upaya Pelestarian Alam - I Ketut Gegel (Litbang STFT Widya Sasana Malang, 2019)
The Dayak community is known as a community that is close to nature, and even, can be said they unite themselves with nature. Nature is a